Collapsing Focal Segmental Glomerulosclerosis in a Patient with Systemic Lupus Erythematosus - Hassan Tariq; Arsalan Rafiq; Giovanni Franchin (Case Reports in Medicine)
We present a case of a 36-year-old female from Ghana who presented with atypical chest pain and shortness of breath and was found to have bilateral transudative pleural effusion and trivial pericardial effusion. Further work-up revealed serological markers consistent with active lupus and negative HIV. She developed rapid deterioration of her renal function requiring dialysis. Her renal biopsy showed collapsing focal segmental glomerulosclerosis with diffuse mesangial proliferative glomerulonephritis, consistent with lupus nephritis class II along with tubular degenerative changes. She was started on high dose steroids and later on mycophenolate mofetil. Her renal function slowly recovered to baseline.